Інститут основ конституційного ладу у системі конституційного права України - Кравчук, В.; Kravchuk, V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглядаються актуальні проблеми сучасної конституційно-правової науки, а саме інститут основ конституційного ладу як основний елемент системи конституційного права України. Запропонована авторська дефініція даної категорії та її юридична кваліфікація. In the article urgent problems of modern constitutional and legal science, in particular institution of bases of the constitutional system as a basic element of system of the constitutional law of Ukraine, have been considered. Author's definition of the mentioned category, and also its legal qualification has been offered. The institution of bases of the constitutional system of Ukraine represents peculiar «constitutional basis» for the constitutional fixing and regulation of other major public relations which are a subject of the constitutional law of Ukraine. The institution of bases of the constitutional system of Ukraine creates legal basis for ensuring constant interrelation between a person, society and the state. Therefore undoubted relevance is gained by the phenomenon of bases of the constitutional system of Ukraine, and first of all its interpretation as constitutional and legal institution. The necessity of systematic research of institution of bases of the constitutional system of Ukraine has been defined not only by practical needs of the state, but also by the current state of domestic legal science, and need for thorough and comprehensive theoretical study of this problem.
Institution of Bases of the Constitutional System in the System of Constitutional Law of Ukraine
Keywords: інститут конституційного права; конституційне право; конституційний лад; основи конституційного ладу; система конституційного права; institution of the constitutional law; constitutional law; constitutional system; bases of the constitutional system; system of the constitutional law